Osteopontin depletion in macrophages perturbs proteostasis via regulating UCHL1-UPS axis and mitochondria-mediated apoptosis - Rentsendorj, Altan; Raedschelders, Koen; Fuchs, Dieu-Trang; Sheyn, Julia; Vaibhav, Vineet; Porritt, Rebecca A.; Shi, Haoshen; Dagvadorj, Jargalsaikhan; de Freitas Germano, Juliana; Koronyo, Yosef; Arditi, Moshe; Black, Keith L.; et al. (Frontiers in Immunology, 2023)
Osteopontin (OPN; also known as SPP1), an immunomodulatory cytokine highly expressed in bone marrow-derived macrophages (BMMΦ), is known to regulate diverse cellular and molecular immune responses. We previously revealed that glatiramer acetate (GA) stimulation of BMMΦ upregulates OPN expression, promoting an anti-inflammatory, pro-healing phenotype, whereas OPN inhibition triggers a pro-inflammatory phenotype. Here, we applied global proteome profiling via mass spectrometry analysis to gain a mechanistic understanding of OPN suppression versus induction in macrophages. We identified over 630 differentially expressed proteins (DEPs) in OPN-knockout (OPNKO) or OPN-primed GA stimulation in macrophages as compared to wild type macrophages. The two topmost downregulated DEPs in OPNKO macrophages were ubiquitin C-terminal hydrolase L1 (UCHL1), a crucial component of the ubiquitin-proteasome system (UPS), and the anti-inflammatory Heme oxygenase 1 (HMOX-1), whereas GA stimulation upregulated their expression. We found that UCHL1, previously described as a neuron-specific protein, is expressed by BMMΦ and its regulation in macrophages was OPN-dependent. Moreover, UCHL1 interacted with OPN in a protein complex. Importantly, the effects of GA activation on inducing UCHL1 and anti-inflammatory macrophage profiles were mediated by OPN. Functional pathway analyses revealed two inversely regulated pathways in OPN-deficient macrophages: activated oxidative stress and lysosome-mitochondria-mediated apoptosis (e.g., ROS, Lamp1-2, ATP-synthase subunits, cathepsins, and cytochrome C and B subunits) and inhibited translation and proteolytic pathways (e.g., 60S and 40S ribosomal subunits and UPS proteins). In agreement with the proteome-bioinformatics data, Western blot and immunocytochemical analyses revealed that OPN deficiency perturbs protein homeostasis in macrophages, inducing apoptosis and inhibiting translation, whereas OPN induction by GA restores cellular proteostasis. Taken together, OPN is essential for macrophage homeostatic balance via the regulation of cell viability, the UCHL1-UPS axis, and protein synthesis, indicating its potential application in immune-based therapy.